Maternal healthcare coverage for first pregnancies in adolescent girls: a systematic comparison with adult mothers in household surveys across 105 countries, 2000–2019 - SV Subramanian; Zhihui Li; Chunling Lu; George Patton; Farnaz Sabet (BMJ Global Health)
Background Effective maternal service delivery for adolescent mothers is essential in achieving the targets for maternal mortality under the Sustainable Development Goals. Yet little is known about levels of maternal service coverage in adolescents compared with adult mothers.Method We used data from 283 Demographic and Health Surveys or Multiple Cluster Indicator Surveys for 105 countries between 2000 and 2019 to estimate the levels and trends of inequality in coverage of five maternal health services between adolescent girls (aged 15–19) and adult mothers (aged 20–34), including receiving four or more antenatal care visits, delivering with skilled birth attendants and receiving a postnatal check-up within 24 hours of delivery.Results We analysed data from 0.9 million adolescent girls and 2.4 million adult mothers. Using the most recent data, we found adolescent girls had poorer coverage across all indicators, with receipt of four or more antenatal care visits 6.5 (95% CI 6.3 to 6.7) percentage points lower than adult mothers, delivery with skilled birth attendants 3.6 (95% CI 3.4 to 3.8) lower and having a postnatal check-up within 24 hours of delivery 3.2 (95% CI 2.8 to 3.6) lower. The coverage was 54.2% (95% CI 53.9 to 54.5) among adolescents for four or more antenatal care visits, 69.7% (95% CI 69.4 to 70.0) for delivery with skilled birth attendants and only 30.0% (95% CI 29.3 to 30.7) for receiving a postnatal check-up within 24 hours of delivery. Country-specific coverage of the maternal services increased over time in most countries, but age-related differences persisted and even worsened in some, particularly in the Western Pacific (eg, Vietnam, Lao, Cambodia and Philippines).Conclusion Even though their pregnancies are of higher risk, adolescent girls continue to lag behind adult mothers in maternal service coverage, suggesting a need for age-appropriate strategies to engage adolescents in maternal care.